Особливості формування системи репутаційного менеджменту в умовах розвитку інтернет-технологій - Чирва, Ю. Ю.; Завербний, А. С.; Chyrva, Y. Y.; Zaverbnyj, A. S. (Видавництво Львівської політехніки, 2022)
Упродовж останніх десятиліть спостерігається тенденція до зростання зацікавленості представників бізнесу своєю репутацією та її впливом на результати діяльності й, відповідно, розвитку в майбутньому. Усвідомлення важливості й цінності репутації із боку керівників сучасного бізнесу зумовлює необхідність пошуку способів створення беззаперечної репутації, її підсилення серед стейкхолдерів та ефективного використання. Таким способом є один з видів соціального управління – управління репутацією, який виник через перехід глобальної ринкової економіки до нової парадигми бізнесу, коли нематеріальні активи будь-якої організації, насамперед її ділова репутація, стають головною конкурентною перевагою та ключовою умовою стабільного розвитку. У статті докладно розглянуто феномен репутації як один із ключових факторів впливу на конкурентоспроможність та ринкову вартість бренду; виявлено сучасні технології та механізми управління репутацією за сучасних умов цифрової реальності.

Over the past decades, there has been a trend towards a growing interest of business representatives in their reputation and its impact on the results of operations and, accordingly, development for the future. Awareness of the importance and value of reputation among the leaders of modern business makes it necessary to find ways to build an undeniable reputation, strengthen it among stakeholders and use it effectively. This method is one of the types of social management - reputation management, which arose in connection with the transition of the global market economy to a new business paradigm, when the intangible assets of any organization, primarily its business reputation, become the main competitive advantage and a key condition for stable development. The article examines in detail the phenomenon of reputation as one of the key factors influencing the competitiveness and market value of a brand; modern technologies and mechanisms of reputation management in the framework of modern conditions of digital reality are revealed. We examined the market, corporate and social aspects of business reputation that underlie the reputational management. Practical tools reputation management will be different for different target audiences depending on the kind of relationship they have with organization and how these relationships affect beliefs and feelings of groups. To do this, the organization must have comprehensive information about its current reputation and about the direction in which changes should be made. The need to form a positive reputation of the company in the face of increasing competition is being updated. The author reveals the essence of reputation and reputation management within the framework of the methodology of the phenomenological sociology of knowledge, it is proposed to understand reputation as a phenomenon of everyday life, as a matter of course knowledge about the merits and (or) shortcomings of an object and reputation management as a process of constructing and maintaining a positive reputation of a person or organization as a social reality. Digital technologies are considered as the main mechanism for constructing a company’s reputation as social knowledge in the modern continuum.
Features of the formation of the reputation management system in the conditions of the development of internet technologies
Keywords: ділова репутація; конкурентна перевага; капіталізація; компоненти репутації; репутаційний менеджмент; управління інформацією та комунікаціями; формування громадської думки; цільові аудиторії; business reputation; competitive advantage; capitalization; reputation components; reputation management; information and communication management; public opinion formation; target audiences; 658.005.336; 658.14; 659.3; 659.4